Answer:
The solution set is {-1, 7}
Explanation:
Rewrite x^2-6x=7 as x^2 - 6x = 7.
Identify the coefficient of the x term; it is -6.
Halve this coeff (obtaining -3)
Square this result (obtaining 9)
Add 9 to x^2 - 6x and then subtract 9 from the result: x^2 - 6x + 9 - 9
Then we have:
x^2 - 6x + 9 - 9 = 7. Add 9 to both sides, obtaining
x^2 - 6x + 9 = 16
Rewrite x^2 - 6x + 9 as the square of a binomial: (x - 3)^2
Then we have
(x - 3)^2 = 16
Taking the square root of both sides, we get
x - 3 = ±4, so that: x = 3 + 4 = 7, and x = 3 - 4 = -1.
The solution set is {-1, 7}.